Law Enforcement, Leadership and Wellbeing Creating Resilience - Hesketh, Ian.; Cooper, Cary L. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book provides practical guidance on establishing wellbeing services and interventions within policing for all of those working in law enforcement, particularly leaders and HR professionals. It also offers insight, provokes thought, and gives guidance on how to navigate and get the most from working life as a police officer or member of police support staff. With a focus on the modern working environment, the book covers the key concepts, history, and practical advice necessary for all those interested in this fascinating field of law enforcement. As workplaces become ever more complex and ambiguous, and the world of work ever more dynamic, understanding how organizations behave and how those in the workplace are likely to respond is key to bringing meaning and purpose to work, the cornerstone of effective policing. The book details how to effectively measure workplace wellbeing in policing and how to interpret and use findings to make improvements and craft interventions. It is a key text for exploring law enforcement, leadership, and wellbeing within policing for all those involved with law enforcement, as well as HR professionals, occupational health professionals, and critically, those with police line management responsibilities. Ian Hesketh is the Wellbeing Lead at the UK College of Policing and the Senior Responsible Owner (SRO) for the National Police Wellbeing Service in the UK. Ian also supports the National Forum for Health and Wellbeing at Manchester University Alliance Business School. He is Honorary Fellow at Durham University Business School and a Visiting Fellow at the Open University Business School. His research interests are centred on wellbeing, resilience, and transformation in the context of policing. Sir Cary L. Cooper is the 50th Anniversary Professor of Organizational Psychology and Health at the Alliance Manchester Business School, University of Manchester, UK, and Past President of the CIPD, President of the Institute of Welfare, and former President of RELATE. He has been advisor to the Home Office on stress in the police service, carried out studies for the Police Federation and the Superintendent's Association and an advisor to the College of Policing on their wellbeing national programme. He is also Chair of the National Forum for Health & Wellbeing at Work comprised of 44 global employers.
Chapter 1. Introduction and key concepts -- Chapter 2. Challenges for Law Enforcement -- Chapter 3. Wellbeing -- Chapter 4. Working Environment - Post Pandemic -- Chapter 5. Leadership and Resilience -- Chapter 6. Conclusions.
Keywords: Criminology; Employee health promotion; Psychology, Industrial; Crime -- Sociological aspects; Strategic planning; Leadership; Crime Control and Security; Employee Health and Wellbeing; Work and Organizational Psychology; Crime and Society; Business Strategy and Leadership